Non-Invasive Iontophoretic Delivery of Cytochrome c to the Posterior Segment and Determination of Its Ocular Biodistribution - Laura Gisela González Iglesias; Siwar Messaoudi; Yogeshvar N. Kalia (MDPI AG, 2022)
The intact porcine eye globe model was used to demonstrate that transscleral iontophoresis could deliver a small protein, cytochrome c (Cyt c), to the posterior segment and to investigate post-iontophoretic biodistribution in the different ocular compartments. The effects of Cyt c concentration (1, 5, and 10 mg/mL), current density (3.5 and 5.5 mA/cm2), and duration of the current application (10 min and 1, 2, and 4 h) were evaluated. The data confirmed that transscleral iontophoresis enhanced the intraocular delivery of Cyt c under all conditions as compared to passive controls (same setup but without the current application). Increasing the Cyt c concentration resulted in a proportional enhancement in the Cyt c delivery. Increasing the current density from 3.5 to 5.5 mA/cm2 increased iontophoretic delivery at a Cyt c concentration of 10 mg/mL but did not appear to do so at 5 mg/mL; this was attributed in part to the effect of melanin binding. Short duration iontophoresis (10 min, 3.5 mA/cm2) of a 10 mg/mL Cyt c solution created a depot in the sclera. When this was followed by a 4 h incubation period, post-iontophoretic Cyt c diffusion from the sclera resulted in a different biodistribution, and Cyt c could be quantified in the posterior segment.